Expressive writing and posttraumatic growth: an Internet-based study - Stockton, Hannah; Joseph, Stephen; Hunt, Nigel (American Psychological Association, 2014)
This study examined the effects of Internet-based expressive writing on posttraumatic growth. Expressive (n = 14) and control writing (n = 10) participants wrote for 15 min on 3 occasions spaced 3 days apart. Measures of intrusive and avoidant thoughts and posttraumatic growth were administered at baseline and 2- and 8-week postintervention follow-ups. Results showed that posttraumatic growth significantly increased from baseline to 8-week follow-up in the expressive writing group, while there was no significant change in levels of posttraumatic growth in the control group. Intrusive and avoidant cognitions did not differ between writing groups. Analyses of language use showed that greater use of insight words was associated with an increase in posttraumatic growth. Findings are consistent with cognitive processing models of expressive writing and have implications for Internet-administered expressive writing.